Pengaruh Kualitas Layanan, Harga Dan Kualitas Sistem Informasi Terhadap Kepuasan Pelanggan Gojek (Studi Kasus Pada Pelanggan Gojek di Kelurahan Tlogomas Malang) - Jangky Dausat; Rois Arifin; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine the effect of service quality, price and quality of information systems on customer satisfaction of Gojek. The population in this study were the Gojek customers in the Tlogomas RW 6, RT 1 and RT 2 Malang. The sample used is some Tlogomas residents with the respondents being Gojek customers. The technique used in sampling is a technique using the Slovin formula, the sample selected is 41 respondents. The data were collected using a questionnaire method. The data analysis method used is multiple regression analysis with the help of SPSS software version 14 (Statistical Products and Service Solutions version 14). The test data used were simultaneous hypothesis testing (f), determination coefficient (R2), and partial hypothesis testing (t). The results showed that the independent variable simultaneously had a significant effect on the dependent variable. Based on the test results of the coefficient of determination, the adjusted R value is 74.7%, while the remaining 25.3% is influenced by other variables not included in this study. Based on the partial test results, three variables have an influence on customer satisfaction, service quality (sig = 0.045), price (sig = 0.005) and information system quality (sig = 0.030) have an effect on customer satisfaction.Keywords: service quality, price, information system quality and customer satisfaction